Korelasi antara Motivasi Belajar dengan hasil Belajar dalam Pembelajaran IPAS Kelas IV Sekolah Dasar Negeri 09 Pontianak Barat - Anggun Beliani; Siti Halidjah; Dyoty Auliya Ghasya (Departement of Mathematics Education, 2024)
This study aims to determine whether or not there is a correlation between learning motivation and student learning outcomes in IPAS learning in class IV C of State Elementary School 09 West Pontianak. The research method used is descriptive method with the research form of relationship studies (Interrelationship Studies) by using correlation studies. The population in this study amounted to 26 students and the sample used amounted to 26 students. The data collection techniques in this study were indirect communication techniques and documentary study techniques. The instrument (data collection tool) of this study is a questionnaire (questionnaire) and based on the results of statistical calculations using a simple correlation calculated using SPSS 25 to calculate the correlation between learning motivation and student learning outcomes obtained rcount of 0.761, while rtable for N = 26 and a significance level of 5% of 0.388 means rcount> rtable or 0.761> 0.388. Based on the results of the study, the correlation between learning motivation and student learning outcomes in IPAS learning in class IV C of State Elementary School 09 West Pontianak is in the sufficient category so that it is considered correlated.